2020
DOI: 10.1136/annrheumdis-2020-218636
|View full text |Cite
|
Sign up to set email alerts
|

Molecular pathways in patients with systemic lupus erythematosus revealed by gene-centred DNA sequencing

Abstract: ObjectivesSystemic lupus erythematosus (SLE) is an autoimmune disease with extensive heterogeneity in disease presentation between patients, which is likely due to an underlying molecular diversity. Here, we aimed at elucidating the genetic aetiology of SLE from the immunity pathway level to the single variant level, and stratify patients with SLE into distinguishable molecular subgroups, which could inform treatment choices in SLE.MethodsWe undertook a pathway-centred approach, using sequencing of immunologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 43 publications
0
32
0
3
Order By: Relevance
“…T lymphocyte differentiation, characterized by HLA, is identified as an independent pathway involved in systemic lupus erythematosus (SLE) susceptibility. Genes in the HLA region dominated associated genes in the T cell differentiation and antigen processing and presentation pathways, which was confirmed by gene-based association testing ( 19 ).…”
Section: Discussionmentioning
confidence: 75%
“…T lymphocyte differentiation, characterized by HLA, is identified as an independent pathway involved in systemic lupus erythematosus (SLE) susceptibility. Genes in the HLA region dominated associated genes in the T cell differentiation and antigen processing and presentation pathways, which was confirmed by gene-based association testing ( 19 ).…”
Section: Discussionmentioning
confidence: 75%
“…Within the past 13 years, genome-wide association and pathway-centered sequencing studies have identified many polymorphisms in interferon pathway genes that predispose an individual to developing SLE, including polymorphisms affecting the STAT4 , IRF3 , and IFNA1 genes [ 70 , 71 , 72 , 73 , 74 ]. While single polymorphisms may not be sufficient to cause autoimmunity alone, accumulating numbers of risk variants may cause the immune system to become overwhelmed, leading to immune dysregulation [ 24 , 75 ].…”
Section: The Interferon Pathway and Its Role In Autoimmunity: Systemic Lupus Erythematosus And Beyondmentioning
confidence: 99%
“…However, for IIM, comprehensive studies investigating this class of genetic variation are lacking. Large-scale targeted sequencing of patient cohorts now represents a valid and accessible approach to explore genetic variation at the lower range of allele frequency (10). Moreover, the tailored implementation of statistical algorithms based on the aggregation of rare variants into specific analysis units allows for accurate modeling of these variants, thus resulting in increased discovery power (11).…”
Section: Introductionmentioning
confidence: 99%